Crime and punishment in the Jim Crow South - Wood, Amy Louise, 1967-; Ring, Natalie J. (University of Illinois Press, 2019)
"In recent years, there has been renewed attention to problems pervading the criminal justice system in the United States. The prison population has grown exponentially since 1970 due to the war on drugs, minimum sentencing laws, and other crime control measures instituted in the 1980s and 1990s. The U.S. now incarcerates more people than any other nation in the world, over 2 million in 2016. African Americans constitute nearly half of those prisoners. This volume contributes to current debates on the criminal justice system by filling a crucial gap in scholarship with ten original essays by both established and up-and-coming historians on the topics of crime and state punishment in the Jim Crow era. In particular, these essays address the relationship between the modern state, crime control, and white supremacy. Essays in the collection show that the development of the modern penal system was part and parcel of Jim Crow, and so are the racial injustices endemic to it. The essays that Wood and Ring have curated enrich our understanding of how the penal system impacted the New South; demonstrate the centrality of the carceral regime in producing racial, gender, and legal categories in the New South; provide insightful analysis of intellectual work around the U.S. prison regime; use the penal system to make a case for Southern exceptionalism; and extend conversations about the penal system's restriction of African American political and civil rights. As a whole, the volume provides a nuanced portrait of the dynamic between state power and white supremacy in the South beyond a story of top-down social control"--